Leiomyomatosis peritonealis disseminata: A case report of recurrent presentation and literature review. (2018) - Ferrario, Luca; Zerbi, Pietro; Angiolini, Maria Rachele; Agarossi, Alberto; Riggio, Eliana; Bondurri, Andrea; Danelli, Piergiorgio
Highlights: Leiomyomatosis peritonealis disseminata can result from laparoscopic myomectomies. Tumor morcellation should be probably reconsidered. In young women hormonal therapy is probably the best approach. Close follow-up is necessary due to the risk of malignant degeneration. Abstract: Introduction: Leiomyomatosis peritonealis disseminata (LPD) is an uncommon disease featured by the presence of multiple nodules of smooth muscle cells scattered in the abdominal cavity. To date only about 150 cases have been reported in literature. We report a case of recurrent LPD after laparotomy. Case presentation: In March 2016 a 36-year-old female, with a history of multiple previous laparoscopic myomectomies, consulted her gynaecologist complaining abdominal pain; a MRI was performed and reported multiple pelvic masses, subsequently excised during laparotomy. The patient refused a total hysterectomy with bilateral salpingo-oopherectomy so a close follow-up was recommended. In November 2017 when a new MRI revealed recurrency of the disease, a second laparotomy is performed and all visible nodules are excised. The histological exam confirms LPD diagnosis. On follow-up after three months the patients is completely asymptomatic. Discussion: Differential diagnosis of LPD is challenging due to its similarity to carcinomatosis and to other benign abdominal disorders. Malignant transformation is rare, but it may occur, so a close follow-up is necessary. Even if there is no consensus regarding the treatment, hormonal therapy is probably the best first line approach, while surgery should be the second choice. Conclusions: LPD is an uncommon but potentially severe disease. In our opinion larger studies are necessary to improve our diagnostic effectiveness and to define the best therapeutic strategy.